Proceedings of the Ocean Drilling Program 1989
DOI: 10.2973/odp.proc.sr.111.154.1989
|View full text |Cite
|
Sign up to set email alerts
|

Seismic-Reflection Structure of the Upper Oceanic Crust: Implications from DSDP/ODP Hole 504B, Panama Basin

Abstract: We investigate the seismic reflectivity structure of the upper oceanic crust by comparing multichannel seismic (MCS) reflection data collected at DSDP/ODP Hole 504B to the results of downhole logging. At this site drilling shows a welldefined change in physical properties at depths within the basement of about 0.5-0.6 km, corresponding to the downward transition from volcanic rocks to dikes. Extensive processing of the MCS data, required to remove high-amplitude side-scattered arrivals, revealed no conclusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…However, comparison of our results with those of normal oceanic crust (e.g. Carlson & Herrick 1990) and those sampled in Hole 504B (Wilkins & Langseth 1983; Salisbury et al 1985; Moos et al 1986; Christensen et al 1989; Collins et al 1989) (Table 5) would suggest that the velocities in the Troodos sheeted dyke complex are significantly less than those in oceanic crust. However the average thicknesses are equivalent.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, comparison of our results with those of normal oceanic crust (e.g. Carlson & Herrick 1990) and those sampled in Hole 504B (Wilkins & Langseth 1983; Salisbury et al 1985; Moos et al 1986; Christensen et al 1989; Collins et al 1989) (Table 5) would suggest that the velocities in the Troodos sheeted dyke complex are significantly less than those in oceanic crust. However the average thicknesses are equivalent.…”
Section: Discussionmentioning
confidence: 46%
“… a Salisbury et al . 1985, b Moos et al 1986, c Wilkins & Langseth 1983, d Christensen et al 1989, e Collins et al 1989. …”
Section: Discussionmentioning
confidence: 99%
“…It is the only hole to penetrate through the volcanic section into the underlying sheeted dike complex, and the site has become a reference section for the petrology, geochemistry, hydrothermal alteration, and magnetic and physical properties of the upper oceanic crust (Anderson, Honnorez, et al, 1982;. Previous drilling results from the site (Dick, Erzinger, Stokking, et al, 1992) and seismic evidence (Becker, Sakai, et al, 1988;Collins et al, 1989;Mutter, 1992) suggested that the bottom of the hole lay within the lower portion of the sheeted dike complex, close to the seismic Layer 2/Layer 3 boundary. It has been thought that this transition coincides with the change downward from sheeted dikes to underlying gabbros, or that it is a metamorphic boundary within gabbros or sheeted dikes (e.g., Fox et al, 1973;Christensen and Salisbury, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…12) show that the seismic layer 2A/2B transition corresponds with a rapid decrease in porosity. The similarity of the RAMESESS results with those from the EPR and from the drilled section of layer 2 in ODP Hole 504b (Collins et al 1998) and the Hess Deep (Francheteau et al 1992), all of which equate the layer 2A event with the base of the extrusive igneous section, suggest that the observations from the RAMESSES area have a similar origin.…”
Section: Reflection Events and Their Originsmentioning
confidence: 58%